Are values stable throughout adulthood? Evidence from two German long-term panel studies. - Oscar Smallenbroek; Adrian Stanciu; Regina Arant; Klaus Boehnke (PLoS ONE, 2023)
Previous studies have used cross-sectional or short-term longitudinal data, resulting in a truncated view of a phenomenon unfolding across the lifespan. We find that, contrary to the consensus in the literature, people's values continue developing in adulthood, albeit at a slower pace than in previous developmental stages. We use longitudinal data sources with two measurement instruments. We show their comparability using confirmatory MDS in Study 1 (N = 1,027). We examined value development using latent growth models in a convenience sample of highly educated German peace activists (Study 2, N = 1,209) and corroborated these with evidence from a representative sample from the German population (Study 3, N = 19,566). We find that all values change up to age 40 consistent with theoretical expectations. We observe that with age, self-transcendence and conservation values increase while self-enhancement values decrease. At the same time, we find a curvilinear pattern for openness to change in Study 2 and an overall decrease in Study 3. Moreover, the developmental trajectory of conservation and of self-enhancement in the German general population differ between those with tertiary and without tertiary education. We discuss the implication of the present findings for research on value development and for interventions.